Вселенная, вечность, время и бесконечность - Лолаев Т. П. (Философия и космология, 2011)
Concepts of eternity, time and endlessness belong to number of the most fundamental and difficult characteristics of a matter. It is no coincidence, therefore at a dawn of the human civilization these categories became a subject of the liveliest interest and steadfast attention.